2015
DOI: 10.3366/soma.2015.0147
|View full text |Cite
|
Sign up to set email alerts
|

‘25 degrees of separation’ Versus the ‘ease of doing it closer to home’: Motivations to Offshore Surrogacy Arrangements Amongst Australian Citizens

Abstract: At present, onshore commercial surrogacy is illegal in all Australian states and territories. By contrast, offshore commercial surrogacy is legal in all bar one territory and two states. As a result, significant numbers of Australian citizens undertake travel each year to enter into commercial surrogacy arrangements. The present paper reports on findings derived from interview data collected with 21 Australian citizens who had children through an offshore commercial surrogacy arrangement, either in India or th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Contrary to the difficulties expected in establishing an emotional connection with the developing surrogacy child due to the geographical distance (Ziv and Freund-Eschar, 2015), the fathers experienced anxiety and frustration only when they perceived the pregnancy as absent and hidden in their everyday life. As a result, they needed more time to feel pregnant and created a 'surrogacy storybook' to overcome the so-called 'tyranny of distance' (Riggs, 2015) from the foetus.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the difficulties expected in establishing an emotional connection with the developing surrogacy child due to the geographical distance (Ziv and Freund-Eschar, 2015), the fathers experienced anxiety and frustration only when they perceived the pregnancy as absent and hidden in their everyday life. As a result, they needed more time to feel pregnant and created a 'surrogacy storybook' to overcome the so-called 'tyranny of distance' (Riggs, 2015) from the foetus.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-four studies reported on people participating in commercial gestational surrogacy; five studies reported on altruistic gestational arrangements; and 12 studies included a combination of arrangement types, although they were predominantly commercial and gestational. Six studies did not specify all surrogacy characteristics (Zandi et al, 2014;Riggs 2015;Riggs et al, 2015;Ivry and Teman, 2018;Lindheim et al, 2019;Golboni et al, 2020;Malmquist and Höjerström, 2020).…”
Section: Participantsmentioning
confidence: 99%
“…Intended parents pursued international surrogacy because arrangements were outlawed in their home country (Carone et al, 2017a), access was restricted to heterosexual couples (Lustenberger, 2017), they were unable to find an altruistic surrogate (Everingham et al, 2014;Jadva et al, 2018), the agreement was unenforceable (Everingham et al, 2014;Jadva et al, 2018) and because international arrangements provided a degree of privacy (Riggs, 2015). Factors that were important to intended parents when deciding which country to pursue surrogacy in included the ability to develop a relationship with the surrogate (Carone et al, 2017a;Jadva et al, 2018) and low costs (Lustenberger, 2016;Jadva et al, 2018).…”
Section: Choosing Surrogacy Destinationmentioning
confidence: 99%
“…Following the rise in reproduction by lesbian women, as well as biomedicalization of lesbian family-making practices (Mamo, 2007, Nordqvist, 2012), the last decade has brought a steady increase in cases of intentional gay father families through surrogacy, both in the USA (Gamson, 2015, Goodfellow, 2015, Lewin, 2009), and in other jurisdictions whose citizens travel abroad for surrogacy (see, e.g., Carone et al, 2016 for Italy; Courduriès, 2016 for France; Gamble, 2016 and Golombok, 2015 for the UK; Murphy, 2015 and Riggs, 2015 for Australia; Nebeling Petersen, 2018 for Denmark; Smietana, 2017b for Spain). Gay fathers may constitute well under 50% of all intended parents through surrogacy alongside a majority of heterosexual parents (e.g.…”
Section: Introductionmentioning
confidence: 99%